Microsoft Technology as an Optimization Tool in Promoting Security and Functionality of the Educational System - Jardas Antonić, Jelena; Antonić, Danijel (International Journal of Emerging Technologies in Learning (iJET), 2008)
Abstract - In the cooperation with the City of Rijeka, the project of analysis of the functional and security situation of information infrastructure has been initiated in 24 schools in the authority of the city. Having completed the multicriteria analysis of the collected data, we have built a model of implementing Microsoft service technologies. The implementation should satisfy the elementary security principles that are required by the security standards today, maximizing functionality of infrastructure and minimizing network administration tasks. Server technology that has been used in this solution is Microsoft Widows 2003 Server R2 and Internet Security and Acceleration Server 2006, as well as the GFI WebMonitor and antivirus.